2022
DOI: 10.7759/cureus.22585
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Myeloma and Renal Failure: Mechanisms, Diagnosis, and Management

Abstract: Multiple myeloma (MM) is the second most common hematologic malignancy that involves monoclonal immunoglobulin (Ig)-producing plasma cells. Due to its multifaceted clinical manifestations and complications, it draws attention to various medical specialties like neurology, nephrology, orthopedics, cardiology, etc. Renal failure (RF) is one of the most common and most serious complications of MM that can be caused either by excess immunoglobulins that are nephrotoxic or some other causes like hypercalcemia, infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 80 publications
(172 reference statements)
0
20
0
Order By: Relevance
“…Serum β2-MG is elevated in RF patients ( 1 ). Therefore, the increase in serum β2-MG in MM patients with RF is probably not only due to tumor burden.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Serum β2-MG is elevated in RF patients ( 1 ). Therefore, the increase in serum β2-MG in MM patients with RF is probably not only due to tumor burden.…”
Section: Discussionmentioning
confidence: 99%
“…However, when serum free light chains exceed the absorption capacity of the proximal tubule, these will cause damage to the proximal tubule cells. Therefore, the key to treating renal damage is to remove the excessive serum free light chain ( 1 ). European studies have shown that the removal of free light chains by prolonged dialysis has no benefit to patients during the follow-up, although these results might be partly attributed to the different chemotherapy regimens of these patients ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations